Uji Perbaikan Retakan Dinding Akibat Geser dengan Kawat Ayam - Fauziah, Rizkya Imro?atul ; Karjanto, Adjib; Djatmika, Boedya (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
The wall is designed as a non-structural filler component but is used as a support load on it. When exposed to high earthquake vibrations, there will be diagonal cracks accompanied by a reduction in strength because Indonesia is a country that has the potential to cause earthquakes. There needs to be repairs and reinforcement on the damaged part, one of which is using a chicken wire reinforcement. This study used experimental descriptive with test specimens in the form of brick wall measuring 50 cm x 50 cm, thickness of 14 cm, and in the middle of plaster planted chicken wire. In the crack gap was given mortar. The result of study are (1) test of shear diagonal strength of brick wall without reinforcement of chicken wire obtained a mean value of 1,16 kg / cm2; (2) test of shear diagonal strength of brick wall with chicken wire strengthening obtained a mean value of 1,21 kg / cm2; (3) test of shear diagonal strength of brick wall repair with reinforced chicken wire obtained a mean value of 4.04 kg / cm2; and (4) there was significant different score at ? = 0,05 of brick wall without reinforcement, with reinforcement, and repair with chicken wire strengthening.